GUJARAT ANAND RICE 14: A HIGH YIELDING, MEDIUM SLENDER WITH STRONG AROMATIC VARIETY - D.B. PRAJAPATI; M. B. PARMAR; D. J. KACHA; R.K.GANGWAR; S. S. THORAT (The Bioscan, 2020)
IET 24619 is notified with popular name “Gujarat Anand Rice 14” by CVRC, New Delhi for commercial cultivation under irrigated transplanted ecosystem. To breed a superior, medium slender variety of rice with better qualities, research was started since from 2002 than evaluated in state as well as national trials viz., SSVT,LSVT, ASG, AVT I ASG and AVT II ASG during 2009-16 at MRRS, AAU, Nawagam with different centers of AICRIP of India. Results showed the supremacy of IET 24619 with grain yield recorded 5108 kg/ha, which is 31.68, 46.36 and 46.78 per cent higher over the national check viz., Shobini (3879 kg/ha); regional check viz. Sugandhdhan 907 (3490 kg/ha) and local check viz., Krishna Kamod (3480 kg/ha), respectively. IET-24619 found mid-early in maturity (137 to 140 days), medium tall (110 cm height), higher number of panicles/m 2 (270.33), number of productive tillers (7.5), test weight (16 g) and length of panicles (26.6cm). The grain quality traits viz., head rice recovery (64.9%), amylose content (23.43%), gel consistency (45 mm), strong aromatic grains having with medium slender milled grains 5.66 mm and with volume expansion ratio 4.7. It was moderately resistance to all rice diseases and tolerant to insects and pests.